plzx ans.....Thnk u....PROVE THE FOLLOWING-:
Attachments:
![](https://hi-static.z-dn.net/files/d66/ccf6aee3d39eb6c73e9783c2bb6b066a.jpg)
Answers
Answered by
1
(1-cosA)(1+secA)
= 1+secA-cosA-secAxcosA
=1+1/cosA-cosA-1/cosAxcosA
=1/cosA-cosA
=1-cos^2A /cosA
=sin^2A/cosA
=sinA x sinA/ cosA
=tanA x sinA=RHS (PROVED)
PLEASE MARK IT AS BRAINLIEST
= 1+secA-cosA-secAxcosA
=1+1/cosA-cosA-1/cosAxcosA
=1/cosA-cosA
=1-cos^2A /cosA
=sin^2A/cosA
=sinA x sinA/ cosA
=tanA x sinA=RHS (PROVED)
PLEASE MARK IT AS BRAINLIEST
Answered by
1
Given LHS = (1 - cosA)(1 + secA).
![(1 - cosA)(1 + \frac{1}{cosA} ) (1 - cosA)(1 + \frac{1}{cosA} )](https://tex.z-dn.net/?f=%281+-+cosA%29%281+%2B+%5Cfrac%7B1%7D%7BcosA%7D+%29)
![(1 - cosA)( \frac{1+cosA}{cosA}) (1 - cosA)( \frac{1+cosA}{cosA})](https://tex.z-dn.net/?f=%281+-+cosA%29%28+%5Cfrac%7B1%2BcosA%7D%7BcosA%7D%29+)
![\frac{(1 - cos^2A)}{cosA} \frac{(1 - cos^2A)}{cosA}](https://tex.z-dn.net/?f=+%5Cfrac%7B%281+-+cos%5E2A%29%7D%7BcosA%7D+)
![\frac{sin^2A}{cosA} \frac{sin^2A}{cosA}](https://tex.z-dn.net/?f=+%5Cfrac%7Bsin%5E2A%7D%7BcosA%7D+)
![\frac{sinA}{cosA} * sinA \frac{sinA}{cosA} * sinA](https://tex.z-dn.net/?f=+%5Cfrac%7BsinA%7D%7BcosA%7D+%2A+sinA)
tanA * sinA.
LHS = RHS.
Hope this helps!
tanA * sinA.
LHS = RHS.
Hope this helps!
Similar questions